Efektivitas Penerapan Model Pembelajaran Game Based Learning Terhadap Kreativitas Belajar IPA Siswa Kelas VII SMPN 2 Kec. Akabiluru - Rahmawati, Suci; Novrianti, Novrianti; Zen, Zelhendri; Masnur, Alkadri (Indo-MathEdu Intellectuals Journal, 2025)
The aim of this research is to assess the effectiveness of the Game Based Learning (GBL) model in enhancing the creativity of seventh-grade students in science subjects. The background of the study reveals that conventional teaching methods, which are still dominated by the teacher's role, lead to low active participation from students. This research employs a quantitative approach with a pre-experimental design involving a single group with pretest and posttest measurements. The subjects of the study are the students of class VII.1 at SMP N 2 in Akabiluru District, selected using purposive sampling techniques. The data collection instruments consist of written tests, a creativity learning questionnaire, and practical evaluations. The analysis results indicate an average creativity score of 97.10 with a standard deviation of 11.331, which falls into the high category (77.68%). The GBL model was implemented through the Wordwall platform, utilizing the Matching Pairs feature. These findings demonstrate that the application of the GBL model is effective in enhancing students' creativity in science subjects.